Bilateral Ewing Sarcoma/Primitive Neuroectodermal Tumor of the Breast: A Very Rare Entity and Review of the Literature - N. Majid; M. Amrani; I. Ghissassi; M. El Cadi; M. El Bouzidi; M. El Kabous; A. Kherbach; H. Errihani (Case Reports in Oncological Medicine)
Peripheral primitive neuroectodermal tumors (PNET) are rare malignant tumors, affecting mostly children and adolescents and have been described in breast in eight case reports only. In this paper, we present a case of bilateral mammary ES/PNET where distinction between primary and metastatic diseases was discussed through a literature review. The aim of this work is to demonstrate that although rare, the possibility of PNET should be kept in mind while evaluating a palpable breast abnormality in a young female.